Instructional Methods for Distance Education - Ricky W. Telg (EDIS, 2012)
Much of the time, teaching with distance education technologies is a matter of adapting the teaching styles and instructional methods teachers have been using for years in the traditional classroom. This revised 5-page fact sheet applies basic teaching principles to distance education technologies. Written by Ricky W. Telg and published by the UF Department of Agricultural Education and Communication, September 2012.